Computer Law Review International : A Journal of Information Law and Technology (Verlag Dr. Otto Schmidt, 2005)
Computer Law Review International is an English-language journal dedicated to international developments in the law of modern information technology. It shows how questions that come up with technological developments are dealt with worldwide. In addition to IT law in Europe, CRI addresses developments, particularly in the USA, and provides information about the multitude of global developments with which other countries are trying to meet the challenges posed by a digital society. International developments are illustrated in summary essays and short updates with background information as well as judicial decisions. CRI takes up topics that go beyond the relevant national legal situation and as such can be anticipatory of international legal developments.